(untitled) (Bioagro, 2026)
This research evaluated the impact of different daily light integral (DLI) levels ranging from 8,6 to 22,68 mol·m⁻²·d⁻¹on the quality of bell pepper (Capsicum annuum L.) seedlings using white LED lighting. The study variables were leaf area index, root-to-shoot ratio, compactness, and quality index. A randomized 2x4 experimental design was used, evaluating two PPFD levels (200 and 350 µmol·m-2·s−1) and four photoperiods (12, 14, 16, and 18 h·d-¹). Eight treatments (DLI) with four replications were applied. The interaction between a PPFD of 200 µmol·m-2·s−1and a 14 h·d⁻¹ photoperiod resulted in a higher leaf area index, while root-to-shoot ratio, compactness, and seedling quality index were highlighted when 350 µmol m⁻²·s−¹ PPFD was combined with the 12 h·d⁻¹ photoperiod. These results are fundamental for controlled-environment agriculture, as they allow for the standardization of lighting protocols that ensure high-vigor seedlings for transplanting, while simultaneously promoting energy efficiency and reducing operational costs in vegetable production.